Alternate wetting and moderate drying increases rice yield and reduces methane emission in paddy field with wheat straw residue incorporation. (14th August 2015) - Chu, Guang; Wang, Zhiqin; Zhang, Hao; Liu, Lijun; Yang, Jianchang; Zhang, Jianhua
Abstract: Wheat residue incorporation into the rice paddy field is becoming a popular practice in rice production in China's main rice‐growing area but risks an increased emission of greenhouse gases. This study investigated if an alternate wetting and moderate drying (AWMD) irrigation regime in rice production reduces CH4 emission and increases grain yield when wheat straw residues are incorporated into rice paddy field. One super rice variety was field‐grown in 2012 and 2013 and subjected to four irrigation and straw incorporation treatments: continuously flooded (CF) without straw incorporation (−S), AWMD without straw incorporation (AWMD−S), then CF with straw incorporation (CF + S) and AWMD + S. When compared with the CF, the AWMD regime increased grain yield and water use efficiency (WUE, grain yield over the amount of water used) by 2.7% and 27.6%, respectively, under −S, and by 18.0 and 50.0%, respectively under +S. The AWMD + S treatment also significantly increased nitrogen use efficiency (NUE) compared with the CF + S treatment. The increase in grain yield, WUE and NUE in the AWMD regime, especially under +S, were attributed mainly to a greater root oxidation activity, deeper root distribution and increases in productive tillers, crop growth rate and nonstructural carbohydrate remobilization during grain filling. There was a total of 0.49 kg N2 O‐N ha −1  more loss in the AWMD than in the CF regime. However, the AWMD regime substantially decreased seasonal CH4 emissions, global warming potential (GWP, including both CH4 and N2 O) and greenhouse gas intensity (grain yield over GWP) by 49.8%, 45.2% and 46.7%, respectively, under −S, and by 57.5, 55.9% and 62.6%, respectively, under +S, when compared with the CF regime. The results demonstrate that the AWMD is an effective practice to increase grain yield and resource‐use efficiency and reduce environmental risks especially, when wheat straw is incorporated into paddy field. Abstract : Wheat residue incorporation into the rice paddy field is becoming a popular practice in rice production in China's main rice‐growing area but risks an increased emission of greenhouse gases. Our results show that an alternate wetting and moderate drying could not only increase grain yield and resource‐use efficiency but also decrease environmental risks by reducing methane emissions, especially under wheat straw incorporation into paddy fields.